2018
DOI: 10.1590/s0100-83582018360100057
|View full text |Cite
|
Sign up to set email alerts
|

Sunflower Residue Incorporation Suppresses Weeds, Enhances Soil Properties and Seed Yield of Spring-Planted Mung Bean

Abstract: Continuous and excessive use of herbicides to control various weed biotypes is posing severe threats to soil and human health. Nevertheless, the strategy of using allelopathic crop residues and water extracts for weed control seems to be a sustainable and friendly option to reduce dependence on synthetic herbicides. In addition to controlling weeds, residues of allelopathic crops positively affected soil health. A two-year field study was carried out to examine the impact of sunflower residues on soil properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
2
5
0
1
Order By: Relevance
“…The sunflower residues increased the amount of the essential nutrients for plant growth (NPK) and those necessary nutrients beneficial for the activity of microorganisms and their proportions. The results align with the results of Ullah et al, 2018 9 which confirmed that sunflower residue incorporation at 6 ton ha -1 improved soil health, suppressed weeds and resulted in better seed yield of spring-planted mung bean. Returning soil fertility naturally is desirable as it is one of the promising strategic solutions to provide it naturally without using chemical fertilizers, which negatively affect the properties of the soil 10 .…”
Section: Soil Nutrient Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The sunflower residues increased the amount of the essential nutrients for plant growth (NPK) and those necessary nutrients beneficial for the activity of microorganisms and their proportions. The results align with the results of Ullah et al, 2018 9 which confirmed that sunflower residue incorporation at 6 ton ha -1 improved soil health, suppressed weeds and resulted in better seed yield of spring-planted mung bean. Returning soil fertility naturally is desirable as it is one of the promising strategic solutions to provide it naturally without using chemical fertilizers, which negatively affect the properties of the soil 10 .…”
Section: Soil Nutrient Analysissupporting
confidence: 90%
“…Experimental data were subjected to one analysis of variance (ANOVA) using the SASS system, version (9). The experiment was conducted in (RCBD) design with four replications.…”
Section: Experimantal Analysismentioning
confidence: 99%
“…All the traits of the sunflower residues showed desired reduction against weed dry matter when differed significantly from the control trait. The result came in line with the results of [22] when found that sunflower residue incorporation caused 44-57% reduction in weed density and 58-70% reduction in weed dry weight compared with the control. However, similar to the results of the weed population density, the lowest dry matter rate was observed with the weed associated with the wheat crop.…”
Section: Weed Dry Mattersupporting
confidence: 88%
“…Genotypic variation, growing conditions, and various plant organs, such as leaves, stems and inflorescences may influence the allelopathic activity of sunflower, which can be both stimulatory (at low concentrations) and inhibitory (Gawronska et al, 2007). Different allelopathic activities were observed among a small set of sunflower hybrids (Anjum and Bajwa, 2008;Silva et al, 2009;Alsaadawi et al, 2012;Ullah et al, 2018). The total concentration of phytotoxins (phenolic compounds) was found to be higher in the most-suppressive potential genotypes compared with the least-suppressive ones.…”
Section: Allelopathymentioning
confidence: 98%
“…Sunflower root exudates also inhibit weed seedling growth, but are less effective than leaf and stem tissue leachates (Leather, 1983). Results indicated that application of sunflower water extracts reduced weed density by 5-26% and weed biomass by 9-31%, while sunflower residue incorporation (4 to 6 t/ha) caused 44-57% reduction in weed density and 58-70% reduction in weed biomass compared with the control (Ullah et al, 2018). Genotypic variation, growing conditions, and various plant organs, such as leaves, stems and inflorescences may influence the allelopathic activity of sunflower, which can be both stimulatory (at low concentrations) and inhibitory (Gawronska et al, 2007).…”
Section: Allelopathymentioning
confidence: 99%